School of life [videorecording (DVD)] - Kahn, Jonathan; Paymer, David; Dear, William, 1944-; Reynolds, Ryan; Vernon, Kate, 1961- (Screen Media Films, 2006)
A heartwarming tale of learning to appreciate every moment we're given. A funny and touching story about life in school, but more importantly, the human spirit.